(untitled) - Daucey, Campbell (Boston, 1910)
This book introduce about a trip to guimaras, a tropical shower, easter festivities, a day at Nagaba, the Monsoon, a week-end a Nagaba, a little earthquake, an evening on the river. Philippine sanitation, native education.
Keywords: Philippines,Philippines; Lịch sử,History